Salaries and job satisfaction of private college and university librarians in Pampanga - Quilala, Michael N.; Santos, Herminia H. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 2001)
This study aimed to find out the salaries and job satisfaction of private college and university librarians in Pampanga. Questionnaires were distributed personally by the researcher and served as the main data gathering instrument followed by some personal interviews with the respondents. The subjects of the study consisted of 38 college and university librarians from eight libraries, licensed and non-licensed. Profile analysis, assessment of librarians' monthly salaries, significance of factors such as age, sex, educational attainment, library tasks/duties performed, and years of service to salary; factors that affect the job satisfaction of librarians and over-all assessment of job satisfaction and salaries were analyzed. To test for the significance of age, gender, educational attainment, library tasks performed and years of service to salary, the Chi-Square Test for Independence was used. To support the findings in the Chi-Square Test, cross-comparison of salary among respondents according to their age, gender, educational attainment, library duties performed and years of service was employed.
The major findings of the study are: the majority of the librarians are predominantly females (32 out of 38), most of the respondents belong to the 26-30 age group and are new in the library profession, majority of the Pampanga librarians had earned their college degree in Pampanga and twenty-four of the respondent librarians finished their BS Education Major in Library Science degree while some were required to take library science units to be able to perform as librarians. The duties that private college and university librarians mostly perform are stack maintenance and administrative duties both with twenty-nine responses (76.31 percent), least performed duty is abstracting with only one response (2.63 percent). For the monthly salary of librarians, the highest that one may receive is over P13,000, the median monthly salary is P9,001-P10,000 while the lowest monthly salary is P5001-P6,000. The factor "harmonious relationship with colleagues" ranked first among the factors that affect the job satisfaction of librarians in Pampanga with thirty-six out of thirty-eight responses (94.73 percent).
The Chi-Square Test for Independence showed that there is a relationship between the educational attainment of respondents and their salaries. Educational attainment is the only variable that significantly influences salary. Age, gender, library tasks performed, and length of service have no relationship to salaries. It was also found out that there is no standardized scheme used by private college and university libraries with regard to the salaries of librarians and some do not even have a budget to purchase library materials.
Lastly, most of the librarians in Pampanga are satisfied with their salary and their job with thirty responses (78.95 percent), six librarians are not satisfied with their salary and their job (15.79 percent) and two librarians (5.26 percent) agreed that they are very satisfied with their salary and their job. It is recommended that professional library organizations should give much attention to the librarians outside Metro Manila such as Pampanga, in order to uplift their working capabilities through seminars and trainings. The school administrators should embark staff development of the librarians through education. The other librarians not only the heads must be given the chance to attend seminars and training for their personal development towards their job.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Librarians -- Job satisfaction -- Philippines -- Pampanga; Librarians -- Salaries, pensions; Libraries -- Philippines -- Pampanga